African ancestry is associated with facial melasma in women: A cross-sectional study - D'Elia, Maria Paula Barbieri [UNESP]; Brandï¿½o, Marcela Calixto [UNESP]; de Andrade Ramos, Bruna Ribeiro [UNESP]; da Silva, Mï¿½rcia Guimarï¿½es [UNESP]; Miot, Luciane Donida Bartoli [UNESP]; dos Santos, Sidney Emanuel Batista; Miot, Hï¿½lio Amante [UNESP] (My University, 2017)
Background: Melasma is a chronic acquired focal hypermelanosis affecting photoexposed areas, especially for women during fertile age. Several factors contribute to its development: sun exposure, sex steroids, medicines, and family history. Melanic pigmentation pathway discloses several SNPs in different populations. Here, we evaluated the association between genetic ancestry and facial melasma. Methods: A cross-sectional study involving women with melasma and an age-matched control group from outpatients at FMB-Unesp, Botucatu-SP, Brazil was performed. DNA was extracted from oral mucosa swabs and ancestry determined by studying 61 INDELs. The genetic ancestry components were adjusted by other known risk factors by multiple logistic regression. Results: We evaluated 119 women with facial melasma and 119 controls. Mean age was 39 ï¿½ 9 years. Mean age at beginning of disease was 27 ï¿½ 8 years. Pregnancy (40%), sun exposure (37%), and hormonal oral contraception (22%) were the most frequently reported melasma triggers. All subjects presented admixed ancestry, African and European genetic contributions were significantly different between cases and controls (respectively 10% vs 6%; 77% vs 82%; p < 0.05). African ancestry (OR = 1.04; 95% CI 1.01 to 1.07), first generation family history (OR = 3.04; 95% CI 1.56 to 5.94), low education level (OR = 4.04; 95% CI 1.56 to 5.94), and use of antidepressants by individuals with affected family members (OR = 6.15; 95% CI 1.13 to 33.37) were associated with melasma, independently of other known risk factors. Conclusions: Facial melasma was independently associated with African ancestry in a highly admixed population.
Keywords: Ancestry; Contraceptives; Gonadal steroid hormones; Hormones; INDEL; Melanosis; Melasma; Oral contraceptives; Pigmentation; Pigmentation disorders; Pregnancy; Skin pigmentation; Ultraviolet rays